Social Advertising in Modern Communication Space - Suprun, V.М.; Suprun, L.V. (Наука та інновації, 2018)
Introduction. The evolutionary progress of the modern society is not conceivable without the cultivation of high sociocultural
values. Therefore, social advertising becomes an information creator in the field of communication space.
Problem Statement. The main problems that need to be solved are elaborating effective mechanisms for the creation
and distribution of social advertising and raising the level of its influence on axiological markers of the society.
Purpose. To study the implementation forms, functions, and effectiveness of social advertising as public conduct
standards represented at the level of mass-communication space.
Materials and Methods. Based on the modern information and communicative space of Ukraine, through empiricism
of the data, the specificity of social advertising has been analyzed.
Results. The main constitutive characteristics, features, and functions of social advertising, as well as channels of
distribution, among which the priority is given to modern mass media, have been identified. The main tasks and the
importance of social advertising in the evolutionary development of society have been established. Social advertising is not
only a marker of democratic and humanistic developments of the society, but also an important investment in the future,
since it performs pedagogical and socio-corrective functions. The efficiency of social impact of advertising depends
essentially on the target audience, its emotional, physical conditions, intellectual level, age, gender, experience, occupation,
etc., and its effectiveness depends on the communication mechanisms of influence on the individual information goals and
information needs of the society.
Conclusions. The constitutive features, origin, tasks, and function of social advertising in the modern communication
space are inspired by evolutionary changes in the dynamic, informational and technical society and are able to engage a
broad segment of mass audience into the solution of global problems. Вступ. Еволюційний поступ сучасного суспільства не можливо уявити без культивування високих соціокультурних цінностей, інформаційним формувачем яких у царині комунікаційного простору стає соціальна реклама.
Проблематика. Основними проблемами, які потребують розв’язання, є вироблення ефективних механізмів
створення та поширення соціальної реклами, підвищення рівня її впливу на аксіологічні маркери суспільства.
Мета. Дослідити форми реалізації, функції та ефективність соціальної реклами як стандартів суспільної поведінки, що репрезентуються на рівні масово-комунікаційного простору.
Матеріали й методи. На матеріалі сучасного інформаційно-комунікаційного простору України через емпірику
даних проаналізовано специфіку соціальної реклами.
Результати. Визначено основні конститутивні ознаки, особливості й функції соціальної реклами, комунікаційні
канали її розповсюдження, серед яких пріоритетне місце посідають сучасні засоби масової комунікації. З’ясовано
головні завдання й значення соціальної реклами в еволюційному розвитку соціуму, оскільки це не лише маркер його
демократичних і гуманістичних зрушень, а й важлива інвестиція в майбутнє, адже саме соціальна реклама виконує
виховну й соціально-корегуючу функції. Встановлено, що ефективність впливу соціальної реклами суттєво залежить
від передбачуваної цільової аудиторії, її психоемоційного, фізичного станів, інтелектуального рівня, віку, статі,
життєвого досвіду, професійної зайнятості тощо, а її результативність — від комунікаційних механізмів впливу на індивіда, інформаційної мети й запитів суспільства.
Висновки. Конститутивні ознаки, виникнення, завдання й функціонування в сучасному комунікаційному просторі соціальної реклами інспіровані еволюційними змінами динамічного, інформаційно-технічного соціуму, здатного
залучати до розв’язання глобальних проблем широкий сегмент масової аудиторії. Введение. Эволюционный прогресс современного общества не возможно представить без культивирования высоких социокультурных ценностей, информационным творцом которых в области коммуникационного пространства
становится социальная реклама.
Проблематика. Основными проблемами, которые необходимо решить, являются выработка эффективных механизмов распространения социальной рекламы, повышение уровня ее влияния на аксиологические маркеры общества.
Цель. Исследовать формы реализации, функции и эффективность социальной рекламы как стандартов общественного поведения, которые представляются на уровне массово-коммуникационного пространства.
Материалы и методы. На материале современного информационно-коммуникационного пространства Украины через эмпирику данных проанализирована специфика социальной рекламы.
Результаты. Определены основные конститутивные признаки, особенности и функции социальной рекламы,
коммуникативные каналы ее распространения, среди которых приоритетное место занимают современные средства
массовой коммуникации. Выяснены главные задачи и значение социальной рекламы в эволюционном развитии социума, поскольку это не только маркер его демократических и гуманистических сдвигов, но и важная инвестиция в
будущее, ведь именно социальная реклама выполняет воспитательную и социально-корректирующую функции. Установлено, что эффективность воздействия социальной рекламы существенно зависит от предполагаемой целевой
аудитории, ее психоэмоционального, физического состояний, интеллектуального уровня, возраста, пола, жизненного
опыта, профессиональной занятости и т.д., а ее результативность — от коммуникативных механизмов влияния на
индивида, информационной цели и информационных запросов общества.
Выводы. Конститутивные признаки, задачи и функционирование в современном коммуникационном пространстве социальной рекламы инспирированы эволюционными изменениями динамического, информационно-технического социума, способного привлекать к решению глобальных проблем широкий сегмент массовой аудитории.